1990
DOI: 10.1111/j.1600-0447.1990.tb03076.x
|View full text |Cite
|
Sign up to set email alerts
|

Female alcoholics. IV. Admission problems and patterns

Abstract: In an age-matched sample of male and female inpatient alcoholics (n = 518) of the same ethnic background, subjects under 35 years of age described significantly more problem areas than older age groups. Elderly subjects over 55 were the least articulate group. The first-ever addiction treatment subjects reported the lowest mean number of years of problem drinking, the lowest mean Michigan Alcoholic Screening Test scores and the lowest mean daily alcohol intakes. They also displayed greater current social stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…However, findings from existing research largely demonstrate detrimental consequences for husbands of problem drinking wives. Specifically, husbands with problem-drinking or alcohol-dependent wives report lower relationship satisfaction, poor partner support, verbal aggression, and physical violence (Blankfield & Maritz, 1990; Klee, Schmidt, & Ames, 1991; Leonard & Roberts, 1998; Miller, Downs, & Gondoli, 1989). …”
Section: Gendermentioning
confidence: 99%
“…However, findings from existing research largely demonstrate detrimental consequences for husbands of problem drinking wives. Specifically, husbands with problem-drinking or alcohol-dependent wives report lower relationship satisfaction, poor partner support, verbal aggression, and physical violence (Blankfield & Maritz, 1990; Klee, Schmidt, & Ames, 1991; Leonard & Roberts, 1998; Miller, Downs, & Gondoli, 1989). …”
Section: Gendermentioning
confidence: 99%
“…Many of the difficulties reported by problem drinking couples are similar to the difficulties reported by couples presenting with marital distress but without alcohol problems. Low relationship satisfaction (Zweben, 1986), frequent and intense arguments, and poor sexual functioning (Blankfield & Maritz, 1990) have been reported by women and men presenting for alcoholism treatment and their partners. Observational studies of the marital discussions of problem drinking couples have identified marked deficits in problem solving and communication skills.…”
Section: Association Of Alcohol Abuse and Relationship Problemsmentioning
confidence: 99%
“…There are some important differences between men and women with drinking problems that may impact upon the nature of their relationship difficulties. Relative to alcohol dependant men, alcohol dependant women are more likely to report problems with anxiety, depression, or grief (Kovach, 1986), and less likely to report work problems, impaired driving, or having a criminal record (Benishek, Bieschke, Stoffelmayr, Mavis, & Humphreys, 1992;Blankfield & Maritz, 1990;Marsh & Miller, 1985;Wilsnack & Wilsnack, 1991). Alcohol dependent women also are more likely than alcohol dependent men to report sexual assault, spouse abuse, and sexual disorders as precipitating their drinking (Beckman, 1976;Wilsnack, 1984).…”
Section: Association Of Alcohol Abuse and Relationship Problemsmentioning
confidence: 99%
“…Furthermore, among people seeking couple therapy for distressed relationships, there is a high incidence of alcohol abuse (Halford & Osgarby, 1993). The marriages of people who abuse alcohol are characterised by low relationship satisfaction (Zweben, 1986), frequent and intense arguments (Blankfield & Maritz, 1990), poor communication (Jacob & Leonard, 1992;Jacob, Ritchey, Cvitkovic, & Blane, 1981;Kelly, Halford, & Young, 2002), and physical aggression (Leonard & Blane, 1992).…”
mentioning
confidence: 99%